2018
DOI: 10.4103/sjg.sjg_23_18
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma expressing human epidermal growth factor receptor in South Asian population

Abstract: Background/Aim:Gastric cancer is the third leading cause of cancer mortality worldwide. Human epidermal growth factor (Her-2/neu) has shown strong therapeutic implication in breast cancer. Although the prevalence of Her-2/neu over-expression in gastric cancer has been reported across the world, it is still unknown from South Asia. The aim of this study is to evaluate Her-2/neu expression in gastric adenocarcinomas and to correlate with various clinicopathological variables.Patients and Methods:A total of 95 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…There was also no statistically significant relation between HER2 overexpression and age group. This observation is consistent with most of the studies published recently ( 15 , 16 , 18 ). This suggests that age plays a minor role, if at all, as an independent factor for initiating Trastuzumab therapy in gastric cancer patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…There was also no statistically significant relation between HER2 overexpression and age group. This observation is consistent with most of the studies published recently ( 15 , 16 , 18 ). This suggests that age plays a minor role, if at all, as an independent factor for initiating Trastuzumab therapy in gastric cancer patients.…”
Section: Discussionsupporting
confidence: 94%
“…A statistically significant correlation of HER2 overexpression was observed with moderately differentiated cancers. Such a correlation has been described previously as well ( 15 , 16 ). However, there are studies which have reported no such association between grade of differentiation and HER2 overexpression ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2,3 The human epidermal growth factor receptor 2 (HER2) is a proto-oncogene located on chromosome 17q21, and it is a potential therapeutic target for advanced HER2-positive GC. 4,5 In 6-35% of all GC patients, gastric lesions have been reported to over-express HER2. [6][7][8][9][10] The status of HER2 expression in gastric lesions is currently evaluated by immunohistochemistry (IHC), silver in situ hybridization (SISH), and fluorescence in situ hybridization (FISH).…”
Section: Introductionmentioning
confidence: 99%
“…5,11,12 It was found to be correlated with tumor grade and location on the intestine, but not with gender, age, tumor location or (tumor node metastasis) TNM stage, depth of invasion, lymph node metastases, and distant metastasis. 4,13 At present, gastroscopic biopsy is the main routine detection method to gain information about the histopathological characteristics of lesions before surgery. However, gastroscopic histopathological findings are influenced by many factors, including site and depth of the specimens and evaluation of the pathologist.…”
Section: Introductionmentioning
confidence: 99%